The Effect of Religiosity and Disposable Income on Interest in Saving Purwakarta Community in Islamic Banks - Khofifah, Nisa Nurramdhiani; Bahrun, Adriansah; Oktriawan, Wawan; Muhammad, Adamu Abubakar (Universitas Muhammadiyah Surakarta, 2023)
This study aims to describe and how the influence of religiosity and disposable income on the intention to save the people of Purwakarta in Islamic banks. The method used in this research is quantitative with a purposive sampling technique, which is used as a sample of 100 people from a population of 430,788 people. The theoretical analysis used for the religiosity variable (X1) is the theory of Huber, S., Huber, and the disposable income variable (X2) uses the theory of Syahputri and Dalimunte and Case E, Fair C.Ray, while the interest in saving variable (Y) using the theory of Kotler and Ferdinand. Based on the results of data analysis, it was concluded that first, religiosity has a positive and significant effect on the intention to save in Islamic banks. It is known that the Sig value for the influence of religiosity (X1) on the interest in saving (Y) is 0.002 0.05 and the tcount is 3.218 ttable 1.985. Secondly, disposable income has a positive and significant effect on the intention to save in Islamic banks. It is known that the Sig value for the influence of disposable income (X2) on the intention to save (Y) is 0.000 0.05 and the tcount value is 7.386 ttable 1.985. Thirdly, religiosity (X1) and disposable income (X2) simultaneously influence the dependent variable, namely the intention to save in Islamic banks (Y). 05 and t-test value is 43.609 t-table 3.09. The influence of religiosity and disposable income on the intention to save is 47.3%.